Mrtyu, parakāla, o gati samparke Śrīśrīṭhākura - Nigamānanda, 1879 or 80-1935 (Sārasvata granthābalī, 1979)
Discourses of a Hindu religious leader and founder of the Assam-Bangiya Saraswat Math, a religious institution, on death, life after death, etc.